농촌 삶의 질 영향 요인의 인과구조 분석 - 최강화 (한국농촌경제연구원, 2012)
This study is about investigating the cause and effect relationship among those factors that affect the quality of rural life. Throughout this process, this study would draw a variety of policies with those potential factors that contribute to enhancing the quality of rural life. The existing studies concerning the quality of rural life are most likely empirical studies about which factors are more effective to improve the quality of rural life. However, the sole method of comparing the factors has limitations to solve the issues of rural life. In order to improve the quality of rural life, it is necessary to approach the issue based on system thinking. Therefore, this study investigates a variety of factors based on existing studies and examines reciprocal relationships between each factors. This study would propose detailed measures for sustainable growth of agriculture and rural life, and also suggest three different aspects of enhancing the quality of rural life: first, the rural community as the industrial area, second, the rural communities as the living space, and finally the rural communities as a welfare society.
Keywords: 농촌 삶의 질; 인과지도; quality of rural life; causal loop diagram